Perbedaan kadar protein, kadar lemak dan nilai pH susu sapi pada daerah dataran tinggi dan dataran rendah di Kabupaten Jombang - Reina Puspita Rahmaniar; Dina Wahyu Nur Aini; Ratna Widyawati; Arif Mardjianto (Jurnal Sains Peternakan, 2021)
ABSTRACT The purpose of this study was to determine the differences in protein content, fat content and pH value of cow's milk in the highlands and lowlands in Jombang Regency. A total of nine samples of cow's milk were taken from two cow milk shelters in different plains to be examined at the Veterinary Public Health Laboratory of the UWKS FKH. The protein content was tested by the formol method, the fat content was tested by the garber method and the pH value of milk was measured by a pH meter. The results showed that the average protein content in the highlands was 3.00% ± 0.012 and the lowlands was 3.20% ± 0.063, and the mean fat content in the highlands was 4.004% ± 0.063 and the lowlands 3.125% ± 0.109, the average pH value in the highlands was 6.7 ± 0.005 and the lowlands was 6.6 ± 0.043, so that the results of the comparison of cow's milk from the highlands and lowlands were analyzed using T test can be seen that there was no significant difference in the pH value and protein content, but in fat content there was a significant difference. Keywords: Cow's Milk, Protein Content, Fat Content, pH Value, Jombang